Author Correction: Majority of human traits do not show evidence for sex-specific genetic and environmental effects. Issue 1 (December 2018) - Stringer, Sven; Polderman, Tinca; Posthuma, Danielle
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.